2016
DOI: 10.1115/1.4032445
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Fluoroscopy for the Assessment of Hindfoot Kinematics

Abstract: Current methods of quantifying foot kinematics during gait typically use markers placed externally on bony anatomic locations. These models are unable to analyze talocrural or subtalar motion because the talus lacks palpable landmarks to place external markers. Alternative methods of measuring these clinically relevant joint motions are invasive and have been limited to research purposes only. This study explores the use of fluoroscopy to noninvasively quantify talocrural and subtalar sagittal plane kinematics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…Shultz et al, used single-plane fluoroscopy to report a maximum of 16 mm translational soft tissue artifact at the navicular, up to 13.2 mm at the calcaneus, and less than 1° rotational artifact in hindfoot and forefoot marker clusters [28]. Fluoroscopy has been used to avoid soft tissue artifact and track talocrural and subtalar motion during gait [29] but such systems are not widely available and much more costly than foot models which can be implemented in standard gait laboratories. Other limitations to these systems include a small field of view and concerns with radiation dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Shultz et al, used single-plane fluoroscopy to report a maximum of 16 mm translational soft tissue artifact at the navicular, up to 13.2 mm at the calcaneus, and less than 1° rotational artifact in hindfoot and forefoot marker clusters [28]. Fluoroscopy has been used to avoid soft tissue artifact and track talocrural and subtalar motion during gait [29] but such systems are not widely available and much more costly than foot models which can be implemented in standard gait laboratories. Other limitations to these systems include a small field of view and concerns with radiation dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The barefoot talocrural sagittal plane kinematics reported in this study are similar in magnitude and trend with those previously reported by our group. 8,9 In a 13-subject study published in 2014, we reported 11.2 degrees of maximum talocrural plantarflexion and −7.5 degrees of maximum dorsiflexion (18.1 degrees of ROM in the sagittal plane). 9 The currently reported maximum plantar and dorsiflexion angles are 9.2 degrees and −7.5 degrees, respectively (16.7 degrees ROM).…”
Section: Discussionmentioning
confidence: 87%
“…This method has previously been shown to have errors less than 2 mm with subject foot progression angles of ±5 degrees. 8 Average foot progression angle for the current study was −1.7 degrees (n=233, 191 dynamic trials and 42 static). These translated points of interest were defined in the sagittal plane of the foot and were then used to describe local coordinate systems for the talus and calcaneus.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Exclusion criteria included any significant injury to the foot/ankle or any previous lower extremity surgery (bilateral). The data capture system consisted of a modified fluoroscopy unit [20] placed within an existing Vicon motion analysis capture volume (Vicon Motion Systems, Inc., Oxford, UK).…”
Section: Methodsmentioning
confidence: 99%